Occupational Matching: A Test of Sorts - McCall, Brian P. (Journal of Political Economy, 1990)
This paper develops a theory of job matching in which matching information has both job-specific and occupation-specific components. If occupational matching is significant, then the theory predicts that for those who have switched jobs but remained in the same occupation, increased tenure in the previous job lowers the likelihood of separation from the current job. These predictions are tested using job tenure data from the National Longitudinal Survey's youth cohort. In general, the data are consistent with the occupational matching hypothesis.